ANALYSIS OF THE MOST COMMON SPELLING ERRORS IN ENGLISH FOR SAUDI STUDENTS: A CASE STUDY OF FOUNDATION YEAR STUDENTS: MOST COMMON SPELLING ERRORS IN ENGLISH FOR SAUDI STUDENTS - Almurashi, Safiah Hamed; Sultan, Najah Yousif (Getsempena English Education Journal, 2023)
Most second language learners of English, including Saudi learners at universities, face some challenges with English writing, especially in spelling. These difficulties are attributed to several causes, such as the differences between English and Arabic .The purpose of the present study is to investigate the most spelling errors made by the first year Saudi female students . Also, to define the main factors behind the weakness of students' spelling. Additionally, to suggest some effective teaching approaches to improve spelling instruction. This study adopted Cook's classification of errors, which categorized errors into four categories: substitution, insertion, omission, and transposition. Participants of this study are 80 female students and ten English language teachers. The data was collected through writing a task and a survey. The analysis of errors revealed that errors of omission were the highest proportion of errors with a percentage of (41.55%), whereas substitution spelling errors occur as the lowest frequency with a percentage of (24.65%). Followed by insertion errors with a percentage of (19.72%). The lowest percentage of errors were related to errors of transposition with the proportion of (14.08%). The major cause of the students' spelling errors was the linguistic differences between English and Arabic.